Impact of Corporate Governance on Credit and Liquidity Risks of Nepalese Commercial Banks - Sethi, Prathana; Chand, Pankaj; Yadav, Ram Janam; Bhandari, Samundra (Nepalese Journal of Economics, 2024)
The study examines the impact of corporate governance on credit risk and liquidity risk of Nepalese commercial banks. Liquidity risk and non-performing loans are selected as the dependent variables. The independent variables are board size, number of board meetings, audit committee size, independent directors, gender diversity and bank size. The study is based on secondary data of 17 commercial banks with 102 observations for the period from 2016/17 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the credit risk and liquidity risk of Nepalese commercial banks. The study showed that independent director has a negative impact on non-performing loan. It shows that increase in the number of independent directors leads to decrease in non performing loan. In addition, gender diversity has a positive impact on non-performing loan and liquidity risk. It shows that higher the number of female directors, higher would be the non-performing loans and liquidity risk. Likewise, bank size has a negative impact on non performing loans and liquidity risk. It indicates that larger the bank size, lower would be the non-performing loans and liquidity risk. Furthermore, number of board meeting has a negative impact on non-performing loans and liquidity risk. It shows that higher the number of board meetings, lower would be the non-performing loans and liquidity risk. Similarly, the results also showed that board size has a positive effect on liquidity risk. It means that increase in board size leads to increase in liquidity risk. However, audit committee size has a negative effect on liquidity risk. It means that increase in audit committee size leads to decrease in liquidity risk.